2013
DOI: 10.3354/meps10151
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale distribution of pelagic fishes relative to a large urban pier

Abstract: Intense shading under large piers is known to negatively affect benthic fishes. However, effects on pelagic fishes are poorly known. We employed the equivalent of acoustic video, dual frequency identification sonar (DIDSON), under a kayak to evaluate the response of pelagic fishes at a large (351 × 255 m) urban pier (Pier 40) in Hudson River. A repeated measures design (322 occupations) sampled 3 transects each across both the northern and southern open water-pier edge-under pier continuum during the day and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Our findings of reduced fish abundances under piers are consistent with those of Able et al (2013), who found reduced pelagic fish abundances under a large pier in the Hudson River estuary, suggesting that these effects occur in other systems. Unlike the Hudson River estuary study (Able et al 2013), we did not find higher predator abundances in areas under piers, but predators were rare overall at the depths and habitats that we sampled, and the effects of piers on predators at greater depths are a potential topic for further investigation in our region.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings of reduced fish abundances under piers are consistent with those of Able et al (2013), who found reduced pelagic fish abundances under a large pier in the Hudson River estuary, suggesting that these effects occur in other systems. Unlike the Hudson River estuary study (Able et al 2013), we did not find higher predator abundances in areas under piers, but predators were rare overall at the depths and habitats that we sampled, and the effects of piers on predators at greater depths are a potential topic for further investigation in our region.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, for each observation, two types of data were recorded: the total number of fish observed (a number from 1 to 1,000) and the encounter (always counting as one, regardless of shoal size). The encounter metric is useful because shoaling behavior is not well understood in the context of habitat selection, and a large group of fish may not be more indicative of habitat use than a single fish (Able et al 2013 Multivariate analysis was conducted in Vegan (Oaksanen et al 2013). Nonmetric multidimensional scaling was used to visualize differences in assemblage structure (1) between seawall sites and reference beaches and (2) among pier, corner, and open sections within seawall sites separately for high-and low-tide data, excluding species that were observed in less than 5% of the surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Total abundances of fish can be substantially reduced in areas shaded by piers (Southard et al . ; Able, Grothues & Kemp ). Juvenile salmon Oncorhynchus spp.…”
Section: Documented Effects Of Overwater Structures On Fishmentioning
confidence: 99%
“…reefs and harbors, though these areas have great ecological significance. For example, natural and man-made structures may offer refugia, e.g., mangrove prop roots (MacDonald et al, 2009), sea-grass beds (Sogard and Olla, 1993) and pile fields (Able et al, 1999), while other altered coastlines (harbors) may prove sub-optimal for fish (Able et al, 2013). Sonar cameras like the DIDSON and ARIS (SoundMetrics Inc.) are valuable tools used to sample fish abundance non-destructively, size and behavior within hard-to-observe, structurally complex, turbid and dark environments.…”
Section: Introductionmentioning
confidence: 99%